DESAIN SISTEM INFORMASI GEOGRAFIS PEMETAAN GIZI BURUK DI KOTA SEMARANG - Bambang Agus Herlambang; Vilda Ana Veria Setyawati (Jurusan Teknologi Informasi Universitas Semarang, 2016)
Severe Protein Energy Malnutrition (PEM) are four major problems in the nutrition world. Such as iodine deficiency disorders, and lack of vitamin A. It also often called malnutrition caused by shortages associated poor dietary intake in terms of quality and quantity. Based on data from Semarang Health Office in 2013, the scope of severe PEM in children under five with BGM (Down Red Lines) of 1,502 (1.7%) and children with severe malnutrition by 32 (0.04%). The number of infants with BGM (Down Red Lines) in Semarang in 2013 was 1,502 or 1.7%. Geographical Information Systems (GIS) is one of the information technology that was designed to use spatial and non spatial data. The system could report information and summarize the malnutrition data thus help to process analysis of the causes of malnutrition in the region. Geographic information systems development method used waterfall method with Unified Modeling tools laguage (UML). System testing was done by white box method for testing complexity groove siklomatis on system design and black box to test the input and output.